2006
DOI: 10.1074/jbc.m511649200
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Is the Link between Frataxin and Iron-Sulfur Deficiency in the Yeast Model of Friedreich Ataxia

Abstract: Friedreich ataxia is a human neurodegenerative and myocardial disease caused by decreased expression of the mitochondrial protein frataxin. Proteomic analysis of the mutant yeast model of Friedreich ataxia presented in this paper reveals that these cells display increased amounts of proteins involved in antioxidant defenses, including manganese-superoxide dismutase. This enzyme shows, however, lower activity than that found in wild type cells. Our results indicate that this lack of activity is a consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
8
51
1
2
Order By: Relevance
“…6A). This induction was also observed previously in ⌬yfh1 mutants (17,44) and may be the consequence of the oxidative stress conditions exerted by iron overload. Enzymatic activities were measured using zymograms, which allow a clear differentiation of both isoenzymes (Fig.…”
Section: Analysis Of Iron Accumulation and Aconitase Activity On Thesupporting
confidence: 55%
See 2 more Smart Citations
“…6A). This induction was also observed previously in ⌬yfh1 mutants (17,44) and may be the consequence of the oxidative stress conditions exerted by iron overload. Enzymatic activities were measured using zymograms, which allow a clear differentiation of both isoenzymes (Fig.…”
Section: Analysis Of Iron Accumulation and Aconitase Activity On Thesupporting
confidence: 55%
“…First, we observed the presence of decreased Mn-SOD activity in ⌬yfh1, which compromise the activity of some iron-sulfur-containing enzymes (17). We also observed that decreased activities of SOD1 and SOD2 contribute to oxidative damage to a specific subset of proteins by increasing the presence of chelatable iron in ⌬yfh1 cells (18).…”
Section: Analysis Of Iron Accumulation and Aconitase Activity On Thementioning
confidence: 87%
See 1 more Smart Citation
“…Iron overload in mitochondria of cells lacking frataxin, a yeast model of Friedreich ataxia, results in MnSOD deficiency and increases oxidative stress sensitivity (Desmyter et al, 2004;Irazusta et al, 2006). However, the analysis of MnSOD showed that its activity was similar in parental and isc1⌬ cells ( Figure 4B).…”
Section: Isc1p Deficiency Increase Iron Levelsmentioning
confidence: 94%
“…The days indication refers to the number of day passed since reaching stationary phase. O 2 À detection was carried out using dihydroethidium 62,63 . One micolitre of cell culture was centrifuged and resuspended in 1 ml PBS buffer plus 0.1% glycerol (4°C).…”
Section: Discussionmentioning
confidence: 99%